2009
DOI: 10.1016/j.vacuum.2009.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic transition metal implanted ZnO: A diluted magnetic semiconductor?

Abstract: Recently theoretical works predict that some semiconductors (e.g. ZnO) doped with magnetic ions are diluted magnetic semiconductors (DMS). In DMS magnetic ions substitute cation sites of the host semiconductor and are coupled by free carriers resulting in ferromagnetism. One of the main obstacles in creating DMS materials is the formation of secondary phases because of the solid-solubility limit of magnetic ions in semiconductor host. In our study transition metal ions were implanted into ZnO single crystals w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…As confirmed by X-ray diffraction 34 highpressure PLD process used in the experiment produces highquality Mn doping of ZnO, free of secondary phases (see Figure S3 in supplementary information). However, standard laboratory X-ray diffraction fails to detect small amounts of dopant-related secondary phases 35 and nanosized precipitations do not produce pronounced peaks in the diffraction pattern. For this reason, the Mn local atomic structure was investigated by Mn K-edge x-ray absorption fine structure.…”
Section: Structure Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…As confirmed by X-ray diffraction 34 highpressure PLD process used in the experiment produces highquality Mn doping of ZnO, free of secondary phases (see Figure S3 in supplementary information). However, standard laboratory X-ray diffraction fails to detect small amounts of dopant-related secondary phases 35 and nanosized precipitations do not produce pronounced peaks in the diffraction pattern. For this reason, the Mn local atomic structure was investigated by Mn K-edge x-ray absorption fine structure.…”
Section: Structure Analysismentioning
confidence: 98%
“…S3 in ESI †). However, standard laboratory X-ray diffraction fails to detect small amounts of dopant-related secondary phases 35 and nanosized precipitations do not produce pronounced peaks in the diffraction pattern. For this reason, the Mn local atomic structure was investigated by Mn K-edge X-ray absorption ne structure.…”
Section: Structure Analysismentioning
confidence: 98%
“…Fe-doped ZnO (Fe:ZnO) film could be an important multi-functional material. Reports about Fe:ZnO thin films focus mostly on ferromagnetic properties [12][13][14][15][16]. Structural, optical, and electrical properties of Fe:ZnO films are relatively less studied [17][18][19] though it merit deeper understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Following the original report by Ueda et al 12, many experiments have been carried out to confirm the theory prediction and the initial result. Some results dealing with RT FM of Fe‐doped ZnO samples have also been published 13–20. However, there remain some questions regarding the origin of the magnetic behavior in these DMS materials.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, Shim et al 19 showed that RT FM in Fe‐doped ZnO with additional Cu doping stems from nanocrystalline ZnFe 2 O 4 with an inverted spinel structure. Zhou et al 20 reported that the metallic α‐Fe nanocrystals may be responsible to the FM in Fe‐implanted ZnO single‐crystal samples. A detailed structural, chemical bonding states, and magnetic investigation with high‐quality codoped samples is essential to resolve the controversy.…”
Section: Introductionmentioning
confidence: 99%